ANALISIS YURIDIS PERLINDUNGAN KONSUMEN ATAS KEBOCORAN DATA PRIBADI DALAM TRANSAKSI JUAL BELI AKUN DOMPET DIGITAL - Bintang Mahacakri Lisan Putri; Rohaini; Putri, Ria Wierma (Program Studi Hukum Universitas Pamulang, 2025)
Consumer protection in the digital era is a major challenge faced by Indonesia along with the rapid development of technology and electronic transactions. Despite the existence of regulations such as the Consumer Protection Law and the Electronic Information and Transaction Law (ITE Law), the current regulations are still unable to address new problems arising from digitalization, such as personal data leakage, online fraud, as well as difficulties in enforcing laws against cross-border digital platforms. This research aims to explore the urgency of law reform to strengthen consumer protection in the digital era. Through a qualitative approach, this research identifies various challenges faced by digital consumers, including a lack of transparency in digital services, low digital literacy, and insufficient supervision of businesses in the digital sector. The findings show that comprehensive legal reforms are needed to strengthen transparency, data security, and make it easier for consumers to access their rights. This reform should also include the establishment of special mediation and arbitration institutions for the digital sector, strengthening supervision of business actors, and harmonization between domestic regulations and international standards. This research concludes that with more responsive and sustainable legal reforms, Indonesia can create a safer, fairer and more reliable digital environment for consumers.